Incomes and inequality in the long run: the case of German elderly - Timm Bönke; Carsten Schröder; Katharina Schulte (Kiel University, Department of Economics, 2008)
We employ German Sample Survey Income data to examine income inequality and the financial situation of elderly citizens for the period from 1978 to 2003, focussing on differences between retired and non-retired elderly and between elderly with residence in the Old and the New German Laender. Inter-temporal changes in income inequality are also decomposed by income sources. To our knowledge, this is the first study that provides comparable and detailed longitudinal income statistics for the German elderly. We find some remarkable inter-temporal patterns. First, the financial situation of the elderly has improved substantially over time. This is true especially for the New Laender, although elderly with residence in the Old Laender remain financially privileged. Within the same age cohort, we also find that non-retired, on average, are financially better-off compared to retired elderly. For reunified Germany, inequality is astonishingly stable over time, but rises significantly since 1993 in the New German Laender.
Keywords: D31; J14; H55; H31; 330; Pensioner; Inequality; Inequality Decomposition; German Sample Survey Income data; Rentner; Alte Menschen; Einkommensverteilung; Vermögen; Deutschland; Alte Bundesländer; Neue Bundesländer